Both isoforms of human UDP-glucose:glycoprotein glucosyltransferase are enzymatically active - Takeda, Yoichi; Seko, Akira; Hachisu, Masakazu; Daikoku, Shusaku; Izumi, Masayuki; Koizumi, Akihiko; Fujikawa, Kohki; Kajihara, Yasuhiro; Ito, Yukishige (Glycobiology (Oxford), 2014)
Being recognized as an important constituent of the glycoprotein folding cycle, uridine diphosphate-glucose:glycoprotein glucosyltransferase (UGGT) has been a subject of intense study. Up to now, it is two isoforms, UGGT1 and 2 have been identified, which share ∼ 50% amino acid identity. UGGT1 is a well-documented enzyme which functions as a folding sensor in the endoplasmic reticulum, by the virtue of its ability to transfer a glucose residue to non-glucosylated high-mannose-type glycans of immature glycoproteins exhibiting non-native conformation. On the other hand, direct evidence to support the glucosyltransferase activity of UGGT2 has been lacking, leaving it unclear as to whether it has any function in the glycoprotein folding process. This study aimed to reveal the property of human UGGT2 by using synthetic substrates such as fluorescently labeled glycans and N-glycosylated proteins. The analysis, for the first time, revealed the glucosyltransferase activity of UGGT2, whose specificity was shown to be quite similar to UGGT1, in terms of both glycan specificity and preferential recognition of proteins having non-native conformations. Finally, Sep15 was found to form the heterodimeric complex with both isoforms of UGGT and markedly enhanced its glucosyltransferase activity.